PROBLEMS IN THE FIELDS OF APPLICATION OF BIOMATERIALS - Tursunpulatova Durdona Azamat qizi, (American Journal of Botany and Bioengineering, 2024)
Biomaterials, which are used extensively in medical and dental applications, offer the promise of improved patient outcomes due to their compatibility with biological tissues. However, the field of biomaterials faces several significant challenges that need to be addressed to fully realize their potential. This article aims to provide an in-depth review of the key problems in the application of biomaterials, including biocompatibility, mechanical properties, degradation, and regulatory issues.